Legal Corruption, Politically Connected Corporate Governance and Firm Performance - Polona Domadenik; Janez Prašnikar; Jan Svejnar (Institute for the Study of Labor (IZA), 2014)
In this paper we present and test a theory of how political corruption, found in many transition and emerging market economies, affects corporate governance and productive efficiency of firms. Our model predicts that underdeveloped democratic institutions that do not punish political corruption result in political connectedness of firms that in turn has a negative effect on performance. We test this prediction on an almost complete population of Slovenian joint stock companies with 100 or more employees. Using the supervisory board structure, together with balance sheet and income statement data for 2000-2010, we show that a higher share of politically connected supervisory board members leads to lower productivity.
Keywords: D2; D21; D73; G34; L32; 330; corruption; corporate governance; productivity; politicians; state owned enterprises